Surgical Intervention Combined With Photodynamic Therapy for Treatment of Perifolliculitis Capitis Abscedens et Suffodiens - Zhaojun Yuan, MM; Kai Xie, MM; Nan Cao, MM; Qingxue Wang, MM; Xuan Guo, MM; Yilei Wu, MM; Honglei Wang, MD; Hong Liu, MD; Guoyan Liu, MD; Guangliang Zhang, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Perifolliculitis capitis abscedens et suffodiens (PCAS) is a chronic recurrent disease. Single treatment modalities are commonly ineffective. A surgical intervention combined with photodynamic therapy (PDT) may be an effective treatment strategy. Herein, we present the case of a 21-year-old man with a 2-month history of PCAS treated with such a treatment. PDT may directly eradicate sebaceous glands and reduce follicular hyperkeratosis, and the surgical procedure can eliminate septic and decayed tissue. The surgical intervention combined with PDT was effective in relieving the patient’s pain, and we believe it provides an option for the treatment of PCAS.